2003
DOI: 10.1046/j.1365-2141.2003.04727.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro aspirin resistance detected by PFA‐100TM closure time: pivotal role of plasma von Willebrand factor

Abstract: SummaryThe in vitro closure time (CT), determined by the Platelet Function Analyzer (PFA-100 TM ), is used to monitor patients treated with aspirin. A relatively high percentage of in vitro aspirin resistance was reported despite an adequate inhibition of platelet response to arachidonic acid and we investigated whether high plasma levels of von Willebrand factor ristocetin cofactor activity (vWF:RCo) may contribute to this profile. Platelet aggregation test, CT [collagen adrenaline (CEPI-CT) and collagen aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
2
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 33 publications
1
59
2
7
Order By: Relevance
“…As a matter of fact, Chakroun et al recently showed that high plasma VWF levels are the main determinant of short PFA-100 closure time in patients with cardiovascular disease on aspirin treatment, 61 and Watala et al demonstrated that VWF interaction with GPIb and GPIIb/IIIa is the major determinant of PFA-100 closure time, whereas other platelet receptors and mechanisms leading to platelet aggregation are of minor significance. 63 These findings explain the relatively high prevalence of short PFA-100 closure time in patients on aspirin treatment for cardiovascular or cerebrovascular disease, 42,43,[57][58][59][60][61][62] because these patients tend to have higher than normal levels of plasma VWF. Therefore, because aspirin does not inhibit the major determinants of the PFA-100 closure time, it appears that the PFA-100 system is not an adequate method to measure platelet inhibition by aspirin.…”
Section: Failure Of Aspirin To Inhibit Platelet Function In Vivo or Imentioning
confidence: 99%
See 3 more Smart Citations
“…As a matter of fact, Chakroun et al recently showed that high plasma VWF levels are the main determinant of short PFA-100 closure time in patients with cardiovascular disease on aspirin treatment, 61 and Watala et al demonstrated that VWF interaction with GPIb and GPIIb/IIIa is the major determinant of PFA-100 closure time, whereas other platelet receptors and mechanisms leading to platelet aggregation are of minor significance. 63 These findings explain the relatively high prevalence of short PFA-100 closure time in patients on aspirin treatment for cardiovascular or cerebrovascular disease, 42,43,[57][58][59][60][61][62] because these patients tend to have higher than normal levels of plasma VWF. Therefore, because aspirin does not inhibit the major determinants of the PFA-100 closure time, it appears that the PFA-100 system is not an adequate method to measure platelet inhibition by aspirin.…”
Section: Failure Of Aspirin To Inhibit Platelet Function In Vivo or Imentioning
confidence: 99%
“…This could easily account for the high percentage of subjects with short closure time despite being on aspirin treatment. 42,43,[57][58][59][60][61][62] Because the PFA-100 system studies platelet function under flow conditions that are characterized by high shear, plasma VWF is a major determinant of closure time. As a matter of fact, Chakroun et al recently showed that high plasma VWF levels are the main determinant of short PFA-100 closure time in patients with cardiovascular disease on aspirin treatment, 61 and Watala et al demonstrated that VWF interaction with GPIb and GPIIb/IIIa is the major determinant of PFA-100 closure time, whereas other platelet receptors and mechanisms leading to platelet aggregation are of minor significance.…”
Section: Failure Of Aspirin To Inhibit Platelet Function In Vivo or Imentioning
confidence: 99%
See 2 more Smart Citations
“…One of the drawbacks is the use of PFA-100 TM testing to assess thrombotic risk because of the fact that it is particularly sensitive to vWF levels [29] and functional testing may be altered if vWF levels are different in the patients studied. Other methods that may provide additional information include ex vivo reperfusion studies, receptor density measurements, and ristocetin induced platelet aggregation however in a previous study, ristocetin induced platelet agglutination was not affected by the HPA-2b polymorphism [7].…”
Section: Limitationsmentioning
confidence: 99%